Study Fenomenologi : Pengalaman Ibu Hamil yang Pertama Kali Terdiagnosis Preeklampsia di RSUD Koja Provinsi DKI Jakarta - Sunarti, Nina; Nugroho, Natsir; Hodikoh, Atik (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
The process of pregnancy will make physical and psychological changes that are complex and require adaptation. Complications that occur in the mother during pregnancy will threaten the welfare of the mother and fetus. One of the many conditions experienced during pregnancy is Eclampsia / preeclampsia which is one of the direct causes of death in mothers. The purpose of this study was to determine the experience of pregnant women who were first diagnosed with preeclampsia, this process will produce an experience for the prospective mother. The research method used is a qualitative research method with a phenomenological approach. Taking participants by purposive sampling, as many as 7 participants were informants. Data collection is done by in-depth interviews (indepht interview). The results of the study, it is known the experience of pregnant women who were first diagnosed with preeclampsia with 7 themes namely the reasons referred and feelings when diagnosed with preeclampsia, understanding, signs or characteristics, family support, culture of preeclampsia, hopes for nursing services, hopes in later life related to preeclampsia experiences. In conclusion, pregnant women who were first diagnosed with preeclampsia expressed feelings of sadness and distrust, not all participants in this study felt the signs and symptoms of preeclampsia. Family support at that time was very meaningful for participants. Family member factors that influence the participant's disease at that time there are those who influence it or not, as well as monthly family income factors. Expectations of mothers to nursing services related to preeclampsia is to get information as early as possible for the prevention of complications in pregnancy. Hope for the next life related to the experience that has been gained can be a lesson for the future so that this case does not recur in the next pregnancy.Keywords: Experience of pregnant women, preeclampsia, risk factors for preeclampsia